Physical performance parameters of young judo athletes: effects of biological maturation and training experience - Athayde, Marina Saldanha da Silva (2024)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Desportos, Programa de Pós-Graduação em Educação Física, Florianópolis, 2024.